Review of the aphids fauna (Hemiptera, Aphidomorpha) of the Kazakh part of the Kungey Alatau ridge (North Tien-Shan) - Кадырбеков, Р.Х.; Колов, С.В. (Fundamental and Experimental Biology, 2023)
At the moment, 111 species of aphids from 55 genera have been identified in the Kazakh part of the Kungey Alatau ridge, represented by the families Adelgidae (1 species, 0.9% of the total number of identified species) and Aphididae (110 species, 99.1%). The family Aphididae is represented by 9 subfamilies: Anoeciinae (1 species, 0.9%), Thelaxinae (2, 1.8%), Eriosomatinae (8, 7.3%), Lachninae (4, 3.6%), Callaphidinae (6, 5.5%), Macropodaphidinae (1, 0.9%), Saltusaphidinae (1, 0.9%), Chaitophorinae (7, 6.4%), Aphidinae (80, 72.7%). In this subfamily, the subfamilies Aphidinae, Chaitophorinae, Eriosomatinae, and Callaphidinae are always the richest in species. The most species have been identified in the genera Aphis (24), Chaitophorus, Macrosiphoniella (species each 7), Brachycaudus (5), Acyrthosiphon, Uroleucon (species each 4), Cinara, Pterocomma, Forda (species each 3). In the remaining 46 genera, 1-2 species were noted. For the first time, 17 species or subspecies are indicated for the Kazakh part of the Kungey Alatau ridge Pemphigus birimatus, Trama rara, Betulaphis brevipilosa, B. quadrituberculata, Therioaphis trifolii, Macropodaphis rechingeri, Saltusaphis scirpus, Chaitophorus horii beuthani, Aphis cisticola, A. salviae, A. taraxacicola, Aphidura alatavica, Rhopalomyzus codonopsidis, Acyrthosiphon cyparissiae turkestanicum, Uroleucon pseudobscurum, Uroleucon jaceae reticulatum, Macrosiphoniella antennata antennata. Betulaphis quadrituberculata the first time for Kazakhstan and North Tien Shan. Chaitophorus horii beuthani the first time for North Tien Shan too. The vertical biotopic distribution, trophic specialization features, and the relative abundance of identified aphid species are also considered. A zoogeographic analysis was made.